2015
DOI: 10.1007/s12187-015-9318-2
|View full text |Cite
|
Sign up to set email alerts
|

The Chain of Relationships Among Gratitude, Prosocial Behavior and Elementary School Students’ School Satisfaction: The Role of School Affect

Abstract: Based on Fredrickson's Broaden-and-Build Theory of Positive Emotion, we explored the role of school affect (i.e., positive affect in school and negative affect in school) in connecting gratitude, prosocial behavior, and school satisfaction among a sample of 324 (176 males) elementary school students in grades 4 to 6 by using structural equation modeling. The participants completed a packet of questionnaires, including the Gratitude Questionnaire (GQ-6), the Elementary School Students' Subjective Well-Being in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 82 publications
1
17
0
2
Order By: Relevance
“…In the present research, satisfaction with clinical practice had a positive correlation with a disposition of gratitude in the participants and a negative correlation with clinical practice stress; a disposition of gratitude also had a negative correlation with clinical practice stress. The result of this study can be interpreted as a result that can support the research of Kong et al, 30 where a path analysis showed that disposition of gratitude in college students ultimately resulted in improved satisfaction with life, including studies; the research of Lee and Kim, 40 which is showed that positive attitudes including gratitude increase enhance satisfaction with Clinical practice; and the research of Tian et al, 41 that students with high dispositional gratitude tend to have high school satisfaction. We also believe that it reconfirms the relationship between satisfaction and clinical practice stress.…”
Section: Discussionsupporting
confidence: 81%
“…In the present research, satisfaction with clinical practice had a positive correlation with a disposition of gratitude in the participants and a negative correlation with clinical practice stress; a disposition of gratitude also had a negative correlation with clinical practice stress. The result of this study can be interpreted as a result that can support the research of Kong et al, 30 where a path analysis showed that disposition of gratitude in college students ultimately resulted in improved satisfaction with life, including studies; the research of Lee and Kim, 40 which is showed that positive attitudes including gratitude increase enhance satisfaction with Clinical practice; and the research of Tian et al, 41 that students with high dispositional gratitude tend to have high school satisfaction. We also believe that it reconfirms the relationship between satisfaction and clinical practice stress.…”
Section: Discussionsupporting
confidence: 81%
“…Higher scores indicated higher levels of school satisfaction. The School Satisfaction subscale has shown sound psychometric properties with Chinese elementary school students ( Tian et al, 2016 ). A CFA was performed to determine the factor structure of the School Satisfaction subscale with the current sample.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that gratitude and elevation both lead to increased altruistic behavior in adults (Schnall, Roper, & Fessler, 2010). Little is known about elevation in adolescence, but gratitude does predict prosocial behavior in children aged 11 years (e.g., Tian, Chu, & Huebner, 2015). Also, young children are able to reason about reciprocity when making prosocial decisions (Martin & Olson, 2015).…”
Section: Kindness and Well-beingmentioning
confidence: 99%